2016
DOI: 10.1073/pnas.1613273113
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose synthase complexes act in a concerted fashion to synthesize highly aggregated cellulose in secondary cell walls of plants

Abstract: Cellulose, often touted as the most abundant biopolymer on Earth, is a critical component of the plant cell wall and is synthesized by plasma membrane-spanning cellulose synthase (CESA) enzymes, which in plants are organized into rosette-like CESA complexes (CSCs). Plants construct two types of cell walls, primary cell walls (PCWs) and secondary cell walls (SCWs), which differ in composition, structure, and purpose. Cellulose in PCWs and SCWs is chemically identical but has different physical characteristics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 41 publications
4
89
0
1
Order By: Relevance
“…For example, the speeds significantly increased during the mid stages of transition ( Figure 2H). These data are very similar to what has independently been reported for the secondary wall CesA7 (Watanabe et al, 2015), but contrast those of Li et al (2016b). Assuming that the speed of the CSCs represents catalytic activity, these findings support a scenario in which an increase in speed of tracking and CesA abundance leads to a major boost in cellulose synthesis, which is compatible with the rapid development and subsequent death of the xylem vessels.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For example, the speeds significantly increased during the mid stages of transition ( Figure 2H). These data are very similar to what has independently been reported for the secondary wall CesA7 (Watanabe et al, 2015), but contrast those of Li et al (2016b). Assuming that the speed of the CSCs represents catalytic activity, these findings support a scenario in which an increase in speed of tracking and CesA abundance leads to a major boost in cellulose synthesis, which is compatible with the rapid development and subsequent death of the xylem vessels.…”
Section: Discussionsupporting
confidence: 89%
“…Assuming that the speed of the CSCs represents catalytic activity, these findings support a scenario in which an increase in speed of tracking and CesA abundance leads to a major boost in cellulose synthesis, which is compatible with the rapid development and subsequent death of the xylem vessels. Li et al (2016b) also studied secondary wall CesA behavior in the VND7-inducible system and concluded that the CSCs moved unidirectionally as "swarms" (referred to as "directionally coherent movement"; Li et al, 2016b) during xylem vessel development. Our data support this report, but it is important to note that the unidirectional movement apparent in CSI1/POM2 was observed both during primary wall synthesis (DMSO treatment; Figure 4) and xylem vessel development and appears to depend on local versus global cell wall synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of cortical microtubules in cellulose microfibril deposition was demonstrated by disruption of cortical microtubules by pharmacological drugs or genetic mutations, which results in alterations in the patterned secondary wall thickening, the localized cellulose synthase accumulation and the normal cellulose microfibril deposition (Burk & Ye, 2002;Roberts et al, 2004;Oda et al, 2005;Wightman & Turner, 2008). Imaging of the fluorescence protein-tagged Arabidopsis secondary wall CESA7 revealed that clusters of CESA complexes moved in the same direction along the cortical microtubule tracks in Arabidopsis epidermal cells induced to undergo transdifferentiation into xylem cells, leading to the suggestion that the coalescence of cellulose microfibrils into macrofibrils in secondary walls is attributed to the clustering of CESA complexes (Watanabe et al, 2015;Li et al, 2016). The alignment of CESAs with the underlying cortical microtubules is mediated by CSI1, a cellulose synthase-interactive protein, which was first discovered as a link between primary wall CESAs and cortical microtubules and subsequently shown to be required for the alignment of secondary wall CESAs with cortical microtubules during the early phase of xylem secondary wall thickening (Li et al, 2015;Schneider et al, 2017).…”
Section: Cellulose Synthase Activity and Cellulose Microfibril Deposimentioning
confidence: 99%
“…Plant cells establish cortical microtubule (MT) arrays that are independent of centrosomes and closely aligned with the plasma membrane in a two-dimensional layer (Ehrhardt, 2008;Wasteneys & Ambrose, 2009;Shaw, 2013). During cell morphogenesis, plant cortical MTs play a crucial role by providing tracks for cellulose synthase complexes in cellulose biosynthesis (Paredez et al, 2006;McFarlane et al, 2014;Watanabe et al, 2015;Li et al, 2016). Additionally, plant cortical MTs are also thought to act as sensors that respond to developmental and environmental stimuli via their dynamic reorganization (Nick, 2013).…”
Section: Introductionmentioning
confidence: 99%